Determination of Activity Concentration of Natural Radionuclides and Radiation Hazards’ Assessment of Building Materials in High Background Radiation Areas of Homa and Ruri, Kenya - Willis Otieno Gor Odongo; Margaret Chege; Nadir Hashim; Shinji Tokonami; Kranrod Chutima; Charles Rotich (The Scientific World Journal)
The areas around Homa and Ruri hills in Homa Bay County in Kenya are associated with high background radiation levels. The activity concentration of the natural radionuclides (226Ra, 232Th, and 40K) in earthen building materials used in the areas of Homa and Ruri hills has been measured using a NaI (Tl) detector in this work. The measured values of radioactivity concentrations are used to estimate the associated radiological risk. The earthen building material samples from Ruri registered relatively high 232Th concentration values averaging 1094 ± 55 Bq/kg, nearly three times those of the samples from Homa. 226Ra level was not significantly different in both regions with Homa reporting 129 ± 10 Bq/kg and Ruri 111 ± 6 Bq/kg. 40K was however higher in the samples from Homa by an approximate factor of 2 relative to those from Ruri where the activity concentration was 489 ± 24 Bq/kg. The radium equivalents for 226Ra, 232Th, and 40K in the samples from Ruri were 111 ± 9, 1564 ± 125, and 38 ± 3 Bq/kg, while in Homa, the values were 129 ± 10, 570 ± 46, and 69 ± 5 Bq/kg, respectively. The calculated value of total radium equivalent in Ruri was 1713 ± 137 Bq/kg which was two times higher than that of Homa. 232Th contributed about 74% and 91% to the total radium equivalent in Homa and Ruri, respectively; thus, it was the one with the largest contribution to radiation exposure in both regions. The average indoor annual effective dose rates were 1.74 ± 0.14 and 3.78 ± 0.30 mSv/y in Homa and Ruri, respectively, both of which were above the recommended safety limit of 1 mSv/y.